Investment gaps in IDB borrowing countries - Francesca Castellani; Marcelo Olarreaga; Ugo Panizza; Yue Zhou (Graduate Institute of International and Development Studies, 2018)
We estimate public investment gaps in a sample of developing countries using a public investment demand function. We then use GDP per capita projections, forecasts of structural transformation, and three SDG targets (poverty, infant mortality and lower secondary school completion) to predict public investment needs in 2030 among IDB borrowing countries. Our estimates suggest that in 2014 the total public investment gap of IDB borrowers was close to 170 billion (3.1 percent of the Region's GDP) and that the gap is expected to surpass 717 billion (6.3 percent of the Region's GDP) by 2030 if the SDGs were to be reached.
Keywords: H54; H63; O16; O54; 330; Investment gaps; Latin America; SDG